2000
DOI: 10.4269/ajtmh.2000.62.561
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito isolates of Ross River virus from Cairns, Queensland, Australia.

Abstract: Abstract. During 1996-1998 60,619 mosquitoes were collected around Cairns, Australia and processed for Alphavirus isolation. Thirty-three isolates of Ross River (RR) virus were made from 9 species, Aedes imprimens, Aedes kochi, Aedes notoscriptus, Aedes vigilax, Culex annulirostris, Culex gelidus, Mansonia septempunctata, Verrallina (formerly Aedes) carmenti, and Verrallina lineatus. Attempts to isolate RR virus from 121 Aedes aegypti were unsuccessful. Twenty-six (79%) of the isolates came from within 1 km of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 17 publications
3
29
0
Order By: Relevance
“…52 It is capable of transmitting Ross River fever, Barmah Forest virus, Murray Valley virus, Kunjin virus and Japanese encephalitis virus to humans. 53,54 Culex annulirostris was responsible for the outbreaks of Japanese encephalitis in the Torres Strait in 1995 and 1998, 55,56 and it was also the most dominant species captured in three different tropical habitat types (rainforest, rainforest edge, and grassland) in far north Queensland 57 and from urban, periurban, and melaleuca swamps 45,58 in the same region. Culex annulirostris is regarded as a generalist species with opportunistic feeding patterns defined by host availability and it can use a wide variety of larval habitats including fresh water swamps, shallow grassland pools, and large artificial containers such as livestock watering tanks.…”
Section: Discussionmentioning
confidence: 99%
“…52 It is capable of transmitting Ross River fever, Barmah Forest virus, Murray Valley virus, Kunjin virus and Japanese encephalitis virus to humans. 53,54 Culex annulirostris was responsible for the outbreaks of Japanese encephalitis in the Torres Strait in 1995 and 1998, 55,56 and it was also the most dominant species captured in three different tropical habitat types (rainforest, rainforest edge, and grassland) in far north Queensland 57 and from urban, periurban, and melaleuca swamps 45,58 in the same region. Culex annulirostris is regarded as a generalist species with opportunistic feeding patterns defined by host availability and it can use a wide variety of larval habitats including fresh water swamps, shallow grassland pools, and large artificial containers such as livestock watering tanks.…”
Section: Discussionmentioning
confidence: 99%
“…The virus was also isolated from a Pteropus bat in Australia (Doherty et al 1966;Messenger et al 2003). Serological surveys and virus isolation by Harley et al (2000) from mosquitoes trapped near a flying fox camp suggested the flying fox Pteropus conspicillatus as a potential reservoir host. These authors also suggest that other vertebrates living in the flying fox camp could also be important reservoir hosts (Harley et al 2000(Harley et al , 2001.…”
Section: Togaviridaementioning
confidence: 99%
“…Serological surveys and virus isolation by Harley et al (2000) from mosquitoes trapped near a flying fox camp suggested the flying fox Pteropus conspicillatus as a potential reservoir host. These authors also suggest that other vertebrates living in the flying fox camp could also be important reservoir hosts (Harley et al 2000(Harley et al , 2001. On the other hand, Ryan et al (1997) showed that the grey-headed flying fox (Pteropus poliocephalus) does not produce a viraemia of sufficient magnitude to be very competent vertebrate hosts of RRV (Ryan et al 1997).…”
Section: Togaviridaementioning
confidence: 99%
See 2 more Smart Citations